(Bio)isosteres of ortho- and meta-substituted benzenes - Diepers, H. Erik; Walker, Johannes C. L. (Beilstein Journal of Organic Chemistry, 2024)
Saturated bioisosteres of substituted benzenes offer opportunities to fine-tune the properties of drug candidates in development. Bioisosteres of para-benzenes, such as those based on bicyclo[1.1.1]pentane, are now very common and can be used to increase aqueous solubility and improve metabolic stability, among other benefits. Bioisosteres of ortho- and meta-benzenes were for a long time severely underdeveloped by comparison. This has begun to change in recent years, with a number of potential systems being reported that can act as bioisosteres for these important fragments. In this review, we will discuss these recent developments, summarizing the synthetic approaches to the different bioisosteres as well as the impact they have on the physiochemical and biological properties of pharmaceuticals and agrochemicals.
Keywords: bioisosteres; drug discovery; meta-benzene; ortho-benzene